'It's always there': A study of the sources and motivations for Australian teens' news consumption. Issue 1 (1st June 2022) - Blakston, Angela; Waller, Lisa
There is much to learn about the news habits of Australian teens and this study contributes to the small body of current research through an exploration of the news-consumption practices of 13‐17-year-olds at a Victorian independent school. In doing so, it explores the complex behaviours of younger people who are immersed in a physical and digital environment where, in their own words, news and information 'is always there'. Through an analysis of focus-group data, informed by Potter's theory of media literacy, this study supports international research findings that teens are aware of a range of daily news sources but mostly experience them incidentally. They purposefully seek news when it is a topic that holds their interest or is somehow personally relevant to them. Other significant findings suggest that Australian teens rely heavily on the search engine Google for news and information and have little to no allegiance to specific news providers. Teens believe 'knowing' the news will become more relevant to them as they get older and take on adult responsibilities.